The soldier and the changing state : building democratic armies in Africa, Asia, Europe, and the Americas - Barany, Zoltan D. (Princeton University Press, 2012)
Zoltan Barany in The Soldier and the Changing State systematically explores, on a global scale, civil-military relations in democratizing and changing states. Looking at how armies supportive of democracy are built, he argues that military is most important institution that states maintain, for without military elites who support democratic governance, democracy cannot be consolidated. Barany also demonstrates that building democratic armies is the quintessential task of newly democratizing regimes. But how do democratic armies come about? What conditions encourage or impede democratic civil-military relations? And how can the state ensure the allegiance of its soldiers? Barany examines experiences of developing countries and the armed forces in the context of major political change in six specific settings: in the wake of war and civil war, after military and communist regimes, and following colonialism and unification/apartheid. He evaluates army-building and democratization experiences of twenty-seven countries and explains which predemocratic settings are most conducive to creating a military that will support democracy.